In vitro fermentation profile and methane production of Kikuyu grass harvested at different sward heights - Marín Gómez, Alejandra; Bindelle, Jérôme; Zubieta, Angel; Correa, Guillermo; Arango, Jacobo; Chirinda, Ngonidzashe; Carvalho, Paulo César De Faccio (Frontiers Media, 2021)
Highly digestible forages are associated with an in vitro low-methane (CH4) rumen fermentation profile and thus the possibility of reducing CH4 emissions from forage-based systems. We aimed to assess the in vitro ruminal fermentation profile, including CH4 production, of the top stratum of Kikuyu grass (Cenchrus clandestinus - Hochst. ex Chiov) harvested at different sward heights (10, 15, 20, 25, and 30 cm). Herbage samples (incubating substrate) were analyzed for their chemical composition, in vitro organic matter digestibility (IVOMD), and morphological components. In vitro incubations were performed under a randomized complete block design with four independent runs of each treatment. Gas production (GP), in vitro dry matter digestibility (IVDMD), CH4 production, total volatile fatty acid (VFA) concentration, and their acetate, propionate, and butyrate proportions were measured following 24 and 48 hours of incubation. Herbage samples had similar contents of organic matter, neutral detergent fiber, and crude protein for all treatments. However, a higher acid detergent fiber (ADF) content in taller sward heights than in smaller sward heights and a tendency for metabolizable energy (ME) and IVOMD to decrease as sward height increased were found. Similarly, the stem + sheath mass tended to increase with increasing sward height. Amongst the nutrients, ME (r = –0.65) and IVDMD (r = –0.64) were negatively correlated with sward height (p < 0.001) and ADF was positively correlated with sward height (r = 0.73, p < 0.001). Both the GP and IVDMD were negatively related to the sward height at both incubation times. Sward heights of Kikuyu grass below 30 cm display an in vitro profile of VFAs high in propionate and low in acetate, with a trend toward lower methane production of CH4 per unit of IVDMD. These findings are important to aid decision-making on the optimal sward height of Kikuyu grass and manage animal grazing with the opportunity to reduce CH4 production.